Evolusi Pasar Pemikiran Al-Ghazali Analisis Transaksi Elektronik (E-Commerce) - Zakiyyah Ilma Ahmad; Sirajul Arifin (IAI Darussalam, 2021)
The purpose of this study is to analyze the evolution of the market from the time of the Prophet until the market is known as e-commerce, the meeting between sellers and buyers in an electronic transaction. By examining Al-Ghazali's thoughts regarding the evolution of the market, in which it still upholds Islamic ethics to conform to Islamic principles. This study uses a literature study instrument which is carried out by collecting data information related to buying and selling practices in e-commerce. The development of marketing evolution is associated with the evolution of the market of Al-Ghazali's thinking. When the market becomes e-commerce, experiencing very rapid development, there is a behavior of activity in the market, various kinds of market evolution, something natural will be perfect if it continues to use sharia principles